Learning to think...thinking to learn - Frost, Frank; Kiernan, Leslie J.; Association for Supervision and Curriculum Development (Alexandria, Va. : ASCD, 2007)
This video illustrates research-based strategies for helping students improve their thinking skills so they can succeed in reaching curriculum standards. The program explains techniques for introducing a thinking skill to students, providing guided practice with appropriate scaffolding, and supporting students in transferring the skill to other subjects or contexts.
Teaching information processing skills (44 min.) -- Teaching critical thinking skills (27 min.) -- Teaching complex thinking strategies (36 min.)
editor, Adam Welch.
DVD format
Keywords: Thought and thinking -- Study and teaching; Critical thinking; Learning